Social Media Marketing, Product Knowledge Dan Fear Of Missing Out (Fomo) Terhadap Cosmetic Purchase Decision - Sariani, Komang Widi; Anggarawati, Sularsih (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The many choices of types of cosmetics on the market will certainly affect consumer attitudes in purchase decisions. The purpose of this research is to analyze and determine the influence of social media marketing, product knowledge and fear of missing out on cosmetic product purchase decisions. This study used quantitative methods and had a sample of 200 respondents who purchased cosmetic products. Based on validity tests with Component matrix, reliability tests with Cronbach's alpha and multiple regression analysis consisting of R square test, F test and t test processed using SPSS, it was found that social media marketing has no effect on purchase decisions, Product knowledge has a positive and significant effect on purchase decisions and fear of missing out does not affect the purchase decision of cosmetic products.